If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(2x + -4) = 19 Reorder the terms: 7x + -1(-4 + 2x) = 19 7x + (-4 * -1 + 2x * -1) = 19 7x + (4 + -2x) = 19 Reorder the terms: 4 + 7x + -2x = 19 Combine like terms: 7x + -2x = 5x 4 + 5x = 19 Solving 4 + 5x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 19 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 19 + -4 5x = 19 + -4 Combine like terms: 19 + -4 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 | | 3x(a-2b)+3b= | | -124=-2p+4(2-5p) | | 8a+3=6a+2 | | -124=2p+4(2-5p) | | 20=5b+8-b | | 2b+7b=9 | | 7u+49=-5u+25 | | X^2y-3xy^2-6x^2y= | | x+2/5+x=2/3 | | 8x-4+3x=8x+14 | | a^2+2a-1=0 | | 11=-13y+3y | | -3y+4+6y= | | 6m+x=24 | | 2m-3=6m-4 | | 8(n-1)=-32 | | X-15=36 | | 2(x+8)=34 | | 3m-3=6m-4 | | 3(4x+4)+7(x-1)= |